2004
DOI: 10.1074/jbc.m403601200
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent Differences in the Internalization of Endothelin A and Endothelin B Receptor Heterodimers

Abstract: Endothelin-1 (ET-1) is a potent vasoactive peptide that acts on endothelin A (ETEndothelins (ET-1, ET-2, and ET-3) 1 are important regulators in the vascular system. They act via two receptors: the endothelin A (ET A ) and endothelin B (ET B ) receptors (1, 2). Although human ET A and ET B receptors share 59% amino acid sequence identity (exceeding 75% at the cytoplasmic face), both receptor subtypes couple to different G proteins and differ in their ligand-induced internalization and intracellular trafficking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 39 publications
6
106
0
1
Order By: Relevance
“…Furthermore, whereas binding of adenosine A1 and purine P2Y1 increases receptor oligomerization from a dimeric basal state (Yoshioka et al, 2002), binding of chemokines to CXCR4 promotes oligomerization from a monomeric basal state . On the other hand, it has also been reported that ligand binding induces the converse effect, so that binding of NPY, TRH and cholecystokinin to their respective receptors induces the dissociation of the assembled dimers/oligomers (Cheng and Miller, 2001;Latif et al, 2001;Berglund et al, 2003) which might be related to further endocytic processes (Gregan et al, 2004). Finally, dimeric state of some receptors remains constitutive and insensitive to ligand binding, as reported for the MTR1 receptor or the murine sst2 and sst3 (Pfeiffer et al, 2001;Ayoub et al, 2002).…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, whereas binding of adenosine A1 and purine P2Y1 increases receptor oligomerization from a dimeric basal state (Yoshioka et al, 2002), binding of chemokines to CXCR4 promotes oligomerization from a monomeric basal state . On the other hand, it has also been reported that ligand binding induces the converse effect, so that binding of NPY, TRH and cholecystokinin to their respective receptors induces the dissociation of the assembled dimers/oligomers (Cheng and Miller, 2001;Latif et al, 2001;Berglund et al, 2003) which might be related to further endocytic processes (Gregan et al, 2004). Finally, dimeric state of some receptors remains constitutive and insensitive to ligand binding, as reported for the MTR1 receptor or the murine sst2 and sst3 (Pfeiffer et al, 2001;Ayoub et al, 2002).…”
Section: Introductionmentioning
confidence: 78%
“…ETA and ETB and are co-expressed in a variety of cells, including ventricular myocytes [38], and can form heterodimers that may differ from receptor monomers, and possibly homodimers, with respect to endocytosis or trafficking itineraries [42,43]. As aortic endothelial cells express only ETB, rat aortic endothelial cells were used to determine if the absence of ETA altered the trafficking of ET:ETB complexes (Figure 4).…”
Section: Trafficking Of Etb In Endothelial Cellsmentioning
confidence: 99%
“…Transient transfection was carried out with LipofectAMINE or with FuGENE 6 essentially as described (9,11). For co-transfections of plasmids encoding the mV 2 R or the hV 2 R mutants with plasmids encoding wild-type or mutant dynamin, the ratio of DNA was 0.7/0.3.…”
Section: Methodsmentioning
confidence: 99%
“…LSM-FRET imaging and fluorescence recovery after photobleaching were performed as described in detail previously (11,14). LSM-FRET imaging was performed with the LSM510 META and for fluorescence recovery after photobleaching we used an inverted microscope (Axiovert 100; Zeiss) equipped with a Plan-Apochromat 63ϫ/1.4 objective, a monochromator (Polychrome II; TILL Photonics, Grä felfing, Germany) and a cooled CCD camera (Imago; TILL Photonics).…”
Section: H]avp Binding Experiments With Membrane Preparations and Witmentioning
confidence: 99%